Robust Quantum Computation with Superconducting Charge Qubits via Coherent Pulses - 冯志波 闫润瑛 (Chinese physics letters, 2010)
To achieve robust gate operations on superconducting charge qubits, we theoretically propose a feasible scheme to realize geometric quantum computation via coherent pulses. Only by adiabatically tuning the microwave pulses applied to the gate capacitance can the Berry phases associated with the system be acquired, from which we construct a universal set of geometric gates. Combining the geometric approach with the coherent pulse technique, robust quantum operations aimed at combating noise errors may be implemented experimentally.